2015
DOI: 10.4315/0362-028x.jfp-14-503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clean-Label Antimicrobials and Nitrite Derived from Natural Sources on the Outgrowth of Clostridium perfringens during Cooling of Deli-Style Turkey Breast

Abstract: Organic acids and sodium nitrite have long been shown to provide antimicrobial activity during chilling of cured meat products. However, neither purified organic acids nor NaNO2 is permitted in products labeled natural and both are generally avoided in clean-label formulations; efficacy of their replacement is not well understood. Natural and clean-label antimicrobial alternatives were evaluated in both uncured and in alternative cured (a process that uses natural sources of nitrite) deli-style turkey breast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Treatments 3 and 4 showed the highest (p<0.05) APC (1.86 and 1.84 Log CFU/g). Lemon extract and vinegar have been shown to have antimicrobial activity by inhibiting the growth of microorganisms ( Jackson et al, 2011 ; King et al, 2015 ; Sullivan et al, 2012a ). King et al (2015) suggested that organic acids, mainly citric acid and acetic acid, found in lemon extract and vinegar may inhibit microbial growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatments 3 and 4 showed the highest (p<0.05) APC (1.86 and 1.84 Log CFU/g). Lemon extract and vinegar have been shown to have antimicrobial activity by inhibiting the growth of microorganisms ( Jackson et al, 2011 ; King et al, 2015 ; Sullivan et al, 2012a ). King et al (2015) suggested that organic acids, mainly citric acid and acetic acid, found in lemon extract and vinegar may inhibit microbial growth.…”
Section: Resultsmentioning
confidence: 99%
“…Lemon extract and vinegar have been shown to have antimicrobial activity by inhibiting the growth of microorganisms ( Jackson et al, 2011 ; King et al, 2015 ; Sullivan et al, 2012a ). King et al (2015) suggested that organic acids, mainly citric acid and acetic acid, found in lemon extract and vinegar may inhibit microbial growth. Citric acid has also been shown to have more effective antimicrobial activity than lactic or acetic acid ( Simpson and Sofos, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our extended ham cooling system, which was based on refrigerated cooling rates of actual ham products with natural-source nitrite, a similar trend was found; the population of vegetative cells did not increase during the 15-h cooling period. Although the antimicrobial effects were not assessed after 15 h, no growth of C. perfringens or L. monocytogenes was previously reported in fully cooked deli-style turkey breast formulated with celery juice nitrates during extended storage at 48C (2,4). In the present study, growth results for S. aureus and L. monocytogenes fill a knowledge gap for controlling vegetative cells of postlethality contaminants during the cooling of naturally cured a Time that the product was exposed to the required temperature zone exceeded the requirements of Appendix B.…”
Section: Resultsmentioning
confidence: 99%
“…perfringens [11,12]. This inhibiting effect is more effective at low pH values [9,13], as beside the general effect of the pH value HNO 2 and NO are formed [14]. As a rule, the multiple hurdle approach is recommended for ensuring food quality (Fig.…”
Section: Introductionmentioning
confidence: 99%